AUDITORÍA DE GESTIÓN AL GOBIERNO AUTÓNOMO DESCENTRALIZADO MUNICIPAL DEL CANTÓN PUYANGO DE LA PROVINCIA DE LOJA, PERIODO 2014 - Cueva Prado, Hilda Belti (2017)
The work of thesis called "AUDIT OF MANAGEMENT TO THE AUTONOMOUS GOVERNMENT DECENTRALIZED MUNICIPAL OF CANTÓN PUYANGO OF THE PROVINCE OF LOJA, PERIOD 2014", was developed in order to verify the compliance with the legal regulations that govern the municipal government, to develop the audit phases Of management, to apply management indicators to measure the levels of efficiency, effectiveness and economy with which the institution carries out its activities; And present the management audit report, containing comments, conclusions and recommendations to assist in institutional decision-making. In order to fulfill the objectives previously described, in the first instance, the regulatory framework applicable to the Autonomous Municipal Decentralized Government of the canton Puyango was investigated. For this purpose, it was inquired about the various legal provisions that are of mandatory compliance for the audited entity, And subsequently, establish the degree of compliance in the development of its activities. In the second instance, the management audit phases were developed, starting with a preliminary knowledge of the institution, which collected relevant data on the operation and structure of the entity, then planned the 5 audit, elaborating the questionnaires and programs , Based on the evaluation of the institution's internal control; In the third phase of the audit, the programs were developed and the questionnaires were applied, in order to establish the audit findings of the institution; In the fourth phase, the management audit report was prepared, with the comments, conclusions and recommendations reached in the execution of the audit. In addition, management indicators were applied to measure the efficiency, effectiveness and economy, with which the Municipal Government carries out its activities. For this purpose, indicators were developed by both the audit team and those adopted by the institution, in order to Ensure an optimal evaluation.